Topikaliserade rums- och tidsadverbial i fornsvenskt lagspråk - texttypiska och informationsstrukturella drag - Sandelin Minna (Finland, 2025)
Topicalization is a common means of bringing about syntactic variation in Old Swedish. In topicalization, a sentence element for which the usual place is in the middle or final field is instead placed in the initial field. In Early Old Swedish and up to the mid-15th century, adverbials were more common than subjects in sentence-initial position. This study analyzes factors connected to genre and information structure that contribute to topicalization of adverbials in Early Old Swedish legal language. These factors are analyzed in relation to the structure of the text.
The data consist of the Uppland law (UL) and are restricted to topicalized spatial and temporal adverbs (n=77). Three research questions are posed: 1) what features connected to genre contribute to topicalization in UL; 2) what functions topicalized spatial and temporal adverbials serve in information structure; and 3) whether there is a relationship between genre features and information structure in Early Old Swedish legal language.
Topicalized spatial and temporal adverbials are significantly more common in main clauses (n=57) than in subordinate clauses (n=20) in UL. Clauses with a topicalized spatial or temporal adverb usually belong to legal declarations; topicalization occurs in both first and second clauses. Two central genre-related motivations for topicalization are textual binding and framing, which means that spatial and temporal adverbs can be used to refer backward and forward in the text. Factors connected with genre also include emphasis and contrast, which in old laws is not just a stylistic technique, but has a further function in shaping the text. The information structure functions of the adverbs studied are background and rheme, with the background function being the most common. The function of theme does not occur in the data. The analysis shows clearly that the genre features are connected with the information structure functions; together they contribute to topicalization in Old Swedish legal language.